1985
DOI: 10.1021/bi00336a043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrostatic pressure on the molecular structure and endothermic phase transitions of phosphatidylcholine bilayers: a Raman scattering study

Abstract: The temperature dependences of the Raman spectra of aqueous dispersions of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) were monitored at different but constant pressures between 1 and 1210 bar. The changes observed in these Raman spectra are discussed in terms of the effects of high pressure on the phase state and molecular structure of lipid bilayers. It is demonstrated that the temperature of the endothermic gel to liquid-crystal phase transition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…On the other hand, the L ␤ I phase is also induced by an application of pressure. It was found that bilayers of CnPCs, such as dimyristoyl-PC (DMPC: C14PC) and dipalmitoyl-PC (DPPC: C16PC), form the fully L ␤ I phase under high pressure [10][11][12][13][14][15][16][17][18]. In the L ␤ I phase, hydrocarbon chains of the CnPC molecules in one of the monolayers constituting a bilayer extend beyond the region of the bilayer midplane and alternately interpenetrate into the other opposing monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the L ␤ I phase is also induced by an application of pressure. It was found that bilayers of CnPCs, such as dimyristoyl-PC (DMPC: C14PC) and dipalmitoyl-PC (DPPC: C16PC), form the fully L ␤ I phase under high pressure [10][11][12][13][14][15][16][17][18]. In the L ␤ I phase, hydrocarbon chains of the CnPC molecules in one of the monolayers constituting a bilayer extend beyond the region of the bilayer midplane and alternately interpenetrate into the other opposing monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid bilayer membranes of diacylphosphatidylcholines (diacylPCs), of which two identical saturated fatty-acid chains are bound to the glycerol backbone by ester linkage, have been thoroughly examined by several physico-chemical techniques [1][2][3][4][5][6][7][8][9]. Such bilayer membranes form various kinds of phases depending upon experimental conditions, and the characteristic gel-phase polymorphism is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this is a transition into a viscous gel phase similar to what has been observed in phospholipid dispersions either under pressure or at low temperatures (e.g. [9][10][11][12][13][14]). The formation of a gel-like structure of OTAB was also suggested by [15] who observed a heat signal in differential scanning calorimetry.…”
Section: Temperature Dependence Of Raman Modesmentioning
confidence: 70%